Sequencing Capital Account Liberalization : Lessons From the Experiences in Chile, Indonesia, Korea, and Thailand - Echeverria, Claudia (IMF Working Papers; Working Paper ;, 1997)
This paper examines issues in sequencing and pacing capital account liberalization and draws lessons from experience in four countries (Chile, Indonesia, Korea, and Thailand). The paper focuses on the interrelationship between capital account liberalization, domestic financial sector reforms, and the design of monetary and exchange rate policy. It concludes that capital account liberalization should be approached as an integrated part of comprehensive reform strategies and should be paced with the implementation of appropriate macroeconomic and exchange rate policies.